The effectiveness of Sarawak Economic Development Corporation (SEDC) business premises programme in developing bumiputera entrepreneur / Mohamad Pisal Jamaludin - Jamaludin, Mohamad Pisal (2002)
Nowadays, Malaysia has become one of the most develop country among the third world country in the world. Several developments programmed made by government put Malaysia in this position. However, this development strongly relates to very hardworking Non-Bumiputera minority in Malaysia. We cannot deny the economic achievement by this minority. In the late 80’s, government hopes that this situation will change. By the year 2010, government target is to achieve effective Bumiputera participation and equity ownership of at least 30%. In this regard, measures will be taken to introduce new programmes, reorentiate, consolidate and streamline existing programmes as well improve the delivery mechanism. This will include the creation and promotion of Bumiputera ventures in the manufacturing and dynamic services sectors. Several programmed for Bumiputera entrepreneurs launch by statutory body in order to arouse this movement. Even though involvement of Bumiputera still at the lower target set by the government where only 21% was achieved but there was a positive result.